The LinkedIn Social network as a space for political communication: Spain, the United States, Norway and Colombia - Villegas Arteaga, Janeth Y. (2019)
During the last year’s social media had an important impact on the political discourse and the communication within the society. Especially social networks are getting used more and more in the political context. However, the studies conducted have been polarized into two social networks (Facebook and Twitter), leaving aside other platforms that have characteristics and elements required to be used in this field. As is the case with LinkedIn, a professional sophisticated network with 610 million users in the world. Because of this great number, this investigation is about the network LinkedIn and its potential use in political communication. Through a descriptive methodology with the quantitative technique, an analysis sheet has been prepared with dimensions and levels based on the characteristics of the network and through qualitative techniques with physical and online interviews, this work will try to demonstrate its operation and His political role.